Ease of Use, Service Features and Information Security Risks Against Interest in Transactions Financial Technology during the Covid-19 Pandemic - Sri Wahjuni Latifah; Hanisyatul Komariyah (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This research aims to determine the effect of ease of use, service features and information security risk on the interest in making transactions using financial technology during the covid-19 pandemic. This research is an associative research with a quantitative approach involving 110 respondents using banking financial technology. Samples were selected using purposive sampling techniques and data were analyzed using multiple linear regression analysis with the help of SmartPLS 3 software. The results of this research show that the ease of use, service features and information security risk variables have a significant influence on the interest in making transactions using financial technology during the covid-19 pandemic.